Comparison of Intravenous Bolus with Infusion Regimen of Oxytocin in Patients Undergoing Elective Cesarean Delivery: Intravenous Bolus with Infusion Regimen of Oxytocin and Elective Cesarean Delivery - Sabir, Sara; Bashir, Munazzah; Maqsood, Umaira; Ashfaq, Shumaila; Asghar, Hafiz Faheem; Rashid, Attiya; Umber, Fatima (Pakistan Journal of Health Sciences, 2026)
Postpartum hemorrhage is one of the leading causes of maternal mortality, and its rate of occurrence increases with the increase in the rates of cesarean section. The main prophylaxis is oxytocin, although the best way to administer it (intravenous bolus or continuous infusion) is the most effective and safe. Objectives: To compare the effectiveness and safety of intravenous bolus with the infusion regimen of oxytocin in patients undergoing elective cesarean delivery. Methods: The quasi-experimental study compared intravenous oxytocin bolus versus continuous infusion for the prevention of postpartum hemorrhage in women undergoing elective cesarean section. Ninety term pregnant women (ASA I–II) were allocated to receive either a 3 IU IV bolus followed by infusion or a 10 IU continuous infusion. The primary outcome was postpartum hemorrhage, while secondary outcomes included uterine tone, additional uterotonic requirement, hemodynamic stability, and maternal side effects. Data were analyzed using SPSS version 26.0, with p<0.05 considered statistically significant. Results: The incidence of postpartum hemorrhage was similar in the bolus (4.4%) and infusion (2.2%) groups (p=0.78), with no significant difference in uterine atony or mean blood loss, indicating comparable uterotonic efficacy. However, hypotension and tachycardia were significantly more frequent in the bolus group (p=0.02 and p=0.03, respectively). Conclusions: Intravenous oxytocin bolus and infusion are equally effective in preventing postpartum hemorrhage and maintaining uterine tone during elective cesarean section; however, continuous infusion offers superior maternal hemodynamic stability with significantly lower rates of hypotension and tachycardia, making it the safer regimen.